The Power of Instructional Materials in Teaching Students’ Speaking Skill - Rina Asrini Bakri; Saiful Saiful; Hamid Ismail; Nur Aeni; St. Asriati AM (Celebes Journal of Language Studies, 2021)
Teaching English is very difficult and it is not an easy job. It is different from another subject as it is not our language. In teaching English, the English teacher should have some strategies and they are supposed to build up the students’ motivation, help and mediate the students with some strategies, techniques, and also method of learning therefore they can reach the language development. In SMAN 1 Bontonompo Selatan Gowa the English teacher contributed such many ways in help their students, the researcher is interested in observing and requiring such the information related to the teaching speaking and formulated this research that analyzed (1) the teachers’ strategy in developing students’ speaking English with instructional material (2) the implementation of instructional material. The research design described through descriptive as the result taken from observation, interview, and documentation. The result of this research finds that the teachers develop their strategy with instructional material and the students have good response towards the strategy.